Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1186/1747-597x-9-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the drivers of and obstacles to the willingness to use cognitive enhancement drugs: the influence of drug characteristics, social environment, and personal characteristics

Abstract: BackgroundThe use of cognitive enhancement (CE) by means of pharmaceutical agents has been the subject of intense debate both among scientists and in the media. This study investigates several drivers of and obstacles to the willingness to use prescription drugs non-medically for augmenting brain capacity.MethodsWe conducted a web-based study among 2,877 students from randomly selected disciplines at German universities. Using a factorial survey, respondents expressed their willingness to take various hypothet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
59
3
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(67 citation statements)
references
References 93 publications
4
59
3
1
Order By: Relevance
“…While previous studies have focused on CE as a coping strategy for dealing with excessive academic demands (Sattler et al 2014;Sattler and Wiegel 2013), this study was the first to quantitatively consider CE and its relation to coping styles more generally. Results found that, in both lifestyle and prescription drug groups, greater reported use of dysfunctional coping strategies was associated with a significantly increased likelihood of engagement in CE drug use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While previous studies have focused on CE as a coping strategy for dealing with excessive academic demands (Sattler et al 2014;Sattler and Wiegel 2013), this study was the first to quantitatively consider CE and its relation to coping styles more generally. Results found that, in both lifestyle and prescription drug groups, greater reported use of dysfunctional coping strategies was associated with a significantly increased likelihood of engagement in CE drug use.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it may be that cognitive enhancement is a coping strategy to deal with the stress and pressure typically associated with university life (Schelle et al 2015). This is reflected in the literature: CE has been examined extensively as a response to academic-related stress (Ford and Schroeder 2009;Forlini et al 2015;Sattler et al 2014;Sattler and Wiegel 2013;Wolff and Brand 2013). Comparatively little is known, however, about the relationship (if any) between enhancement drug use and coping.…”
Section: Introductionmentioning
confidence: 99%
“…This is in line with the finding that students who reported having used drugs to improve performance while studying had difficulties to meet the study demands and perceived persistently high performance pressure (Maier et al, 2013;Middendorff et al, 2012). Moreover, pronounced procrastination and high cognitive test anxiety, both characteristics that support chronic stress, increased the willingness to use drugs for PCE among students (Sattler et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, participants were asked about past and current diagnoses of mental health disorders (ADHD, narcolepsy, depression, anxiety disorder, and substance use disorder) that are known to be treated with medications that the scientific literature often refers to as neuroenhancement drugs (Rabiner et al, 2009b;Sattler et al, 2014). A dichotomous variable was used in the analysis to represent the current use of a prescription drug to treat at least one of the aforementioned mental disorders (yes or no).…”
Section: Mental Health and Health Behaviormentioning
confidence: 99%
See 1 more Smart Citation